Measurements and Simulations on the Mechanisms of Efficiency Losses in HIT Solar Cells. (8th June 2015) - Pierro, Silvio; Scuto, Andrea; Valenti, Luca; Foti, Marina; Battaglia, Anna; Mannino, Giovanni; Gerardi, Cosimo; Crupi, Felice; Lombardo, Salvatore
Abstract : We study the electrical and the optical behavior of HIT solar cell by means of measurements and optoelectrical simulations by TCAD simulations. We compare the HIT solar cell with a conventional crystalline silicon solar cell to identify the strengths and weaknesses of the HIT technology. Results highlight different mechanisms of electrical and optical efficiency losses caused by the presence of the amorphous silicon layer. The higher resistivity of the a-Si layers implies a smaller distance between the metal lines that causes a higher shadowing. The worst optical coupling between the amorphous silicon and the antireflective coating implies a slight increase of reflectivity around the 600 nm wavelength.